1981
DOI: 10.1139/m81-160
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fixation and hydrogen metabolism by Rhizobium leguminosarum isolates in pea root nodules

Abstract: A survey of 108 isolates of Rhizobium leguminosarum was conducted to determine the variation in H2 uptake and relative efficiency of N2 fixation in Pisum sativum L. root nodules and the relation of relative efficiency to plant dry weight and N content. Only 14 of the isolates exhibited significant uptake hydrogenase activity and none of these had sufficient hydrogenase activity to recycle all of the H2 produced by nitrogenase. In 74 of the isolates tested relative efficiencies of N2 fixation were less than 0.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 0 publications
2
40
0
Order By: Relevance
“…Roxane were surface-sterilized (Chalifour & Nelson, 1987) and inoculated at sowing with 1 ml per seed of 3-d-o!d cultures of R. leguminosarum bv. viciae grown in modified Yeast Mannitol Broth medium (Nelson & Child, 1981) at 27 °C. Three seeds were planted per jar and thinned to one plant after seedling emergence (6 or 9 d after planting for the high and low temperature regimes, respectiv'ely).…”
Section: Plant Grozvthmentioning
confidence: 99%
“…Roxane were surface-sterilized (Chalifour & Nelson, 1987) and inoculated at sowing with 1 ml per seed of 3-d-o!d cultures of R. leguminosarum bv. viciae grown in modified Yeast Mannitol Broth medium (Nelson & Child, 1981) at 27 °C. Three seeds were planted per jar and thinned to one plant after seedling emergence (6 or 9 d after planting for the high and low temperature regimes, respectiv'ely).…”
Section: Plant Grozvthmentioning
confidence: 99%
“…This strain has been variously described in the literature as exhibiting Hup+ (3,23,24,26) and Hup-(14) phenotypes on P. sativum. Each of the groups studying strain 128C53 used a different pea cultivar as a host …”
Section: Introductionmentioning
confidence: 99%
“…This strain has been variously described in the literature as exhibiting Hup+ (3,23,24,26) and Hup- (14) photon flux density (400-700 nm) of 650 ,uE* m-2 s. Seeds were sterilized, germinated, and selected for uniformity before planting in sterile 750-ml Leonard jars containing vermiculite (10). All plants were provided with sterile N-free nutrient solution (10) and a single strain of Rhizobium in the Leonard jar.…”
mentioning
confidence: 99%
“…Differences in RE2 have been attributed to the ability of some Rhizobium strains to produce an uptake hydrogenase enzyme which can recycle some or all of the H2 produced by nitrogenase (6, 1 1). Using single pea genotypes, Nelson and Child (17) and Ruiz-Argueso et al (19) (17). In one series of experiments with strain 128C52, open plastic pots were used for plant culture rather than Leonard jars.…”
Section: Methodsmentioning
confidence: 99%
“…Other reports indicate that the host plant genotype can alter the expression of the Hup gene in R. leguminosarum strains (1, 3). In some studies with peas, relatively high RE values have been reported even in symbioses having no measurable Hup activity, (2,(8)(9)(10)17), and these high efficiencies are considered to reflect a more efficient allocation of electrons to the reduction of nitrogen by nitrogenase. The RE of pea-Rhizobium symbioses can also be altered by environment and plant age.…”
Section: Introductionmentioning
confidence: 99%